2020
DOI: 10.1111/nzg.12271
|View full text |Cite
|
Sign up to set email alerts
|

Same same, but different? Cycling and e‐scootering in a rapidly changing urban transport landscape

Abstract: This paper explores whether e-scooters can be considered similar to cycling in terms of their demographic appeal and skills required. Building on a social practices approach, we hypothesise that e-scootering and urban cycling may appeal to a similar demographic and require similar competencies. We draw on data from a 2019 survey of users and non-users of e-scooters. Respondents are not more likely to use an e-scooter if they have cycling experience. E-scooters seem to appeal to a broader demographic than cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…For instance, a study in Vienna found that the majority of e-scooter users in Vienna are male, young, and highly educated [14]. Similarly, shared e-scooters in New Zealand seem to appeal more to younger males [48]. Non-academic work in the US [20] and in France [39] showed similar patterns.…”
Section: User Characteristicsmentioning
confidence: 96%
See 2 more Smart Citations
“…For instance, a study in Vienna found that the majority of e-scooter users in Vienna are male, young, and highly educated [14]. Similarly, shared e-scooters in New Zealand seem to appeal more to younger males [48]. Non-academic work in the US [20] and in France [39] showed similar patterns.…”
Section: User Characteristicsmentioning
confidence: 96%
“…Non-academic work in the US [20] and in France [39] showed similar patterns. Moreover, some studies highlighted a positive correlation between e-scooter use and higher levels of education [48,49].…”
Section: User Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…--* Respondents could choose more than one trip purpose; ** trip purpose was not analyzed separately, however, it was classified by mode substitution in each trip purpose which is summarized in "Mode Substitution" column; *** the first number is the likelihood of choosing that mode for the last e-scooter trips and the second number is the travel mode change in general since the e-scooter emerged in the city (multiple choice is allowed for the second one). * Multiple choice is allowed; ** in [58] the numbers are for all respondents in the survey however, in [59], the numbers are only for e-scooter users; *** the data description has not been reported thoroughly in the paper; **** some papers have provided sociodemographic characteristics for only e-scooter users and others for the whole respondents which has been mentioned in this table.…”
Section: Usage Frequency-based User Typesmentioning
confidence: 99%
“…Infrastructures such as dockless bike or e-scooter rental systems have the potential to transform urban mobility systems in all sorts of ways. Curl and Fitt's (2020) article gives an initial overview of how dockless e-scooters have been taken up in Auckland and Christchurch. The promise of new platform based micromobility technologies is that they will introduce a range of sustainable mobility modalities-cycling amongst them-to new demographics of users.…”
mentioning
confidence: 99%